Reading forough farrokhzad ‘s poetry from the perspective of systemic functional linguistics - Forough Hassanpour; Ruzy Suliza Hashim (Penerbit UKM, 2012)
Forough Farrokhzad was one of the most important poets in twentieth century (1935-1976) in Iran. A poet, who for the first time in the history of Persian literature broke boundaries, wrote from a feminine point of view and accentuated the experiences of being a woman. In this paper, we aim to explore her depiction of women in “Green Delusion” through a stylistic and lexico-grammatical method known as “transitivity” which is one of the most prominent part of Halliday’s Systemic Functional Linguistic approach. We have shown in the present study how socially constructed meaning and linguistic structure in the poetic discourse is related. By focusing on the microelements of words, we reveal the poet’s stance toward the situation of women in her society. The findings reveal that many of Farrokhzad’s poems represent feminine sensibility, voicing the inner self of a woman who speaks about love, hate, death and life, simultaneously. Her poetic gesture in most of her poetry was totally feminine.